Insecticidal control of the mealybug Phenacoccus gossypiphilous (Hemiptera: Pseudococcidae), a new pest of cotton in Pakistan - Saeed, Shafqat (Bahauddin Zakariya University, Multan, Pakistan), E-mail: bumblebeepak@hotamil.com; Ahmad, Munir (Bahauddin Zakariya University, Multan, Pakistan); Ahmad, Mushtaq (Nuclear Institute of Agriculture and Biology, Faisalabad, Pakistan); Kwon, Y.J. (Kyungpook National University, Daegu, Republic of Korea) (Entomological research, 2007)
The mealybug Phenacoccus gossypiphilous (Stanley) played havoc with the cotton crop in Pakistan during 2005. To control this pest, insecticides of different groups were evaluated in both the laboratory and in field conditions. In the laboratory, bifenthrin, profenofos and chlorpyrifos proved to be the best insecticides for mealybug control, based on their susceptibility with the leaf dip method for their LC∧50. In field conditions, the recommended application rates of methomyl, profenofos and chlorpyrifos provided the best control: the lethal time studies proved their efficiency for better and timely control of this sporadic pest.